Taṭwīr al-Wasā’il al-Taʿlīmīyah “Al-Podcast al-ʿArabī” li-Taḥsīn Mahārat al-Istimāʿ al-ʿArabīyah li-Ṭalabat al-Madrasah al-Mutawassiṭah al-Islāmīyah - Ikraama, Niswa; Maslamah, Maslamah (Alsina : Journal of Arabic Studies, 2023)
This research focuses on developing "Arabic Cast," an audio learning media presented as an Android application, aimed at enhancing listening skills in Arabic for 10th grade students at Muhammadiyyah Al-Kautsar Senior High School's Special Program in Kartasura. The ADDIE research and development model guided the study through Analysis, Design, Development, Implementation, and Evaluation stages. The study involved all 10th graders of the program. Data collection included validation questionnaires from media experts, student response questionnaires, and pre- and post-test results in oral and written exams. Quantitative analysis and t-tests were used for data interpretation. Key findings include the successful design of "Arabic Cast" as a user-friendly Android application and its effectiveness in improving students' listening skills. Validation by media experts indicated a 90% approval rate, while student response rate was 81%. Significant improvements in listening skills were evidenced by pretest and posttest results, showing a statistical significance of 0.000 0.05. The study concludes that "Arabic Cast" is an effective and appealing tool for enhancing Arabic listening skills among high school students.